2019
DOI: 10.1002/chir.23124
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐cell biocatalytic of Bacillus cereus WZZ006 strain to synthesis of indoxacarb intermediate: (S)‐5‐Chloro‐1‐oxo‐2,3‐dihydro‐2‐hydroxy‐1H‐indene‐2‐carboxylic acid methyl ester

Abstract: In this study, a newly isolated strain screened from the indoxacarb‐rich agricultural soils, Bacillus cereus WZZ006, has a high stereoselectivity to racemic substrate 5‐chloro‐1‐oxo‐2,3‐dihydro‐2‐hydroxy‐1H‐indene‐2‐carboxylic acid methyl ester. (S)‐5‐chloro‐1‐oxo‐2,3‐dihydro‐2‐hydroxy‐1H‐indene‐2‐carboxylic acid methyl ester was obtained by bio‐enzymatic resolution. After the 36‐hour hydrolysis in 50‐mM racemic substrate under the optimized reaction conditions, the e.e.s was up to 93.0% and the conversion was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Tang et al explored a newly isolated B. cereus zju 4-2 strain for use in the efficient transformation of vitamin D3 to 25-hydroxyvitamin D3, providing a high yield [ 44 ]. Zhang et al reported a new biocatalytic route via Bacillus cereus WZZ006 whole cells for the preparation of ( S )-5-chloro-1-oxo-2,3-dihydro-2-hydroxy-1H-indene-2-carboxylic acid methyl ester, an important chiral intermediate of indoxacarb synthesis [ 45 ]. However, to the best of our knowledge, this is the first time that Bacillus cereus was reported as whole cell biocatalyst for use in the production of anti-Prelog chiral alcohols from prochiral ketones.…”
Section: Resultsmentioning
confidence: 99%
“…Tang et al explored a newly isolated B. cereus zju 4-2 strain for use in the efficient transformation of vitamin D3 to 25-hydroxyvitamin D3, providing a high yield [ 44 ]. Zhang et al reported a new biocatalytic route via Bacillus cereus WZZ006 whole cells for the preparation of ( S )-5-chloro-1-oxo-2,3-dihydro-2-hydroxy-1H-indene-2-carboxylic acid methyl ester, an important chiral intermediate of indoxacarb synthesis [ 45 ]. However, to the best of our knowledge, this is the first time that Bacillus cereus was reported as whole cell biocatalyst for use in the production of anti-Prelog chiral alcohols from prochiral ketones.…”
Section: Resultsmentioning
confidence: 99%